2000
DOI: 10.2746/042516400777612099
|View full text |Cite
|
Sign up to set email alerts
|

Equine dental disease Part 3: a long‐term study of 400 cases: disorders of wear, traumatic damage and idiopathic fractures, tumours and miscellaneous disorders of the cheek teeth

Abstract: Of 400 horses referred because of dental disorders, 349 cases were diagnosed as suffering from primary disorders of their cheek teeth. Details of 104 of these cases are presented, including 44 cases with abnormalities of wear, 26 cases with traumatic damage, 24 cases with idiopathic fractures and 10 cases with miscellaneous cheek teeth disorders including oral tumours. The long-term response to treatment was excellent in most cases, even in cases with residual secondary periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
6
10

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(178 citation statements)
references
References 12 publications
10
152
6
10
Order By: Relevance
“…5. Focal overgrowths (FOs) of the cheek teeth (Penzhorn, 1984), which frequently occur as overgrowths at positions 106/206 and 311/411 (Baker, 1979;Dixon, 2002) Step mouth (StM) whereby a cheek tooth overgrows, often because the equivalent tooth on the opposing arcade is missing or damaged (Dixon et al, 2000;Du Toit et al, 2009). 10.…”
Section: Generalised Incisor Overgrowths (Gios) the Authorsmentioning
confidence: 99%
“…5. Focal overgrowths (FOs) of the cheek teeth (Penzhorn, 1984), which frequently occur as overgrowths at positions 106/206 and 311/411 (Baker, 1979;Dixon, 2002) Step mouth (StM) whereby a cheek tooth overgrows, often because the equivalent tooth on the opposing arcade is missing or damaged (Dixon et al, 2000;Du Toit et al, 2009). 10.…”
Section: Generalised Incisor Overgrowths (Gios) the Authorsmentioning
confidence: 99%
“…Tooth fracture secondary to caries is mostly seen in horses aged 9-10 years (Dacre et al 2007;Dixon et al 2007). It occurs due to severe caries that weakens the tooth and makes it more vulnerable to mastication forces (Dixon et al 2000a). In Sweden, caries in 106/206 was associated with a specific bacteria, namely Streptococcus devriesei (Lundstrom et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, foul breath and halitosis was one of signs that were found in dental tartar, sharp enamel points, dental caries, rostral hook, periodontal disease, diestemata, incisor tooth fracture, bit seat, caudal hook and canine tooth fracture, this result was coincide with that mentioned by (pence, 2002). On the other hand Dixon et al (2000a) and Dixon et al (2000b) indicated that halitosis may be present only if widespread periodontal disease, or less commonly, when advanced dental caries is present.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders of wear are sharp enamel points, step mouth (Dixon and Dacre, 2005), smooth mouth (Kempson et al, 2003), wave mouth and shear mouth (Peter et al, 2011), hooks (ramps) (Koontz, 2016) and Bit seat (Bettiol and Dixon, 2011). Diseases of cheek teeth are Trauma (Dixon et al, 2000a), fracture, Periodontal disease, dental tumors (Dixon and Dacre, 2005), dental decay (Timothy and Joseph, 2014), dental plaque(tartar) and dental foreign body (Saulez et al, 2009). Treatment of sharp enamel points, rostral hooks and caudal hooks involved reducing the overlong portion of the tooth by power float and dealing with bit seat by rounding and carefully smoothing rostral corners of the upper, lower #6s help in good performance in bit .…”
Section: Introductionmentioning
confidence: 99%